2023
DOI: 10.3847/1538-4357/ace71e
|View full text |Cite
|
Sign up to set email alerts
|

Black Hole Accretion with Saturated Magnetic Pressure and Disk Wind

Jiahui Huang,
Hua Feng,
Wei-Min Gu
et al.

Abstract: We construct an analytical black hole accretion disk model that incorporates both magnetic pressure and disk wind, which are found to be important from numerical simulations. A saturated magnetic pressure that relates the Alfvén velocity with local Keplerian velocity and gas sound speed is assumed in addition to radiation and gas pressures. The mass accretion rate is assumed to have a power-law form in response to mass loss in the wind. We find three sets of self-consistent solutions that are thermally stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…The effects of magnetic fields on accretion disks have been extensively studied, and some early research (Ferreira & Pelletier 1995;Ferreira 1997;Jacquemin-Ide et al 2019;Huang et al 2023b) found that magnetic winds can significantly decrease the accretion timescale. This finding has been confirmed by numerical simulations (Jacquemin-Ide et al 2021;Scepi et al 2023) and has been used to explain observed phenomena such as young stellar objects (Combet & Ferreira 2008;Martel & Lesur 2022) and X-ray binaries (Ferreira et al 2006;Marcel et al 2018).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The effects of magnetic fields on accretion disks have been extensively studied, and some early research (Ferreira & Pelletier 1995;Ferreira 1997;Jacquemin-Ide et al 2019;Huang et al 2023b) found that magnetic winds can significantly decrease the accretion timescale. This finding has been confirmed by numerical simulations (Jacquemin-Ide et al 2021;Scepi et al 2023) and has been used to explain observed phenomena such as young stellar objects (Combet & Ferreira 2008;Martel & Lesur 2022) and X-ray binaries (Ferreira et al 2006;Marcel et al 2018).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…One class attributes QPO to geometric effects, with the Lense-Thirring precession model of the inner flow being one of the most popular in this category. Initially proposed by Stella & Vietri (1998), this model was further developed by Ingram et al (2009), considering a precessing accretion flow within a truncated accretion disk (Esin et al 1997;Huang et al 2023). While successfully applied to some sources for explaining QPO properties, Nathan et al (2022) recently discovered a very small truncated radius in GRS 1915+105, which does not match the prediction of this model.…”
Section: Introductionmentioning
confidence: 99%